2019
DOI: 10.7554/elife.44702
|View full text |Cite
|
Sign up to set email alerts
|

CNS myelination and remyelination depend on fatty acid synthesis by oligodendrocytes

Abstract: Oligodendrocytes (OLs) support neurons and signal transmission in the central nervous system (CNS) by enwrapping axons with myelin, a lipid-rich membrane structure. We addressed the significance of fatty acid (FA) synthesis in OLs by depleting FA synthase (FASN) from OL progenitor cells (OPCs) in transgenic mice. While we detected no effects in proliferation and differentiation along the postnatal OL lineage, we found that FASN is essential for accurate myelination, including myelin growth. Increasing dietary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
85
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 55 publications
0
85
0
1
Order By: Relevance
“…SREBP1, like other SREBPs, is activated by a reduction of intracellular cholesterol, indicating a homeostatic link between fatty acid synthesis and cholesterol synthesis [108,109]. De novo fatty acid synthesis is critical for the correct formation and growth of myelin both in the PNS and in the CNS [33,48,[110][111][112]. Animals ablated for fatty acid synthase (encode by Fasn) in either Schwann cells or oligodendrocytes present a partial block in the onset and efficiency of myelination.…”
Section: Fatty Acid Synthesismentioning
confidence: 99%
See 1 more Smart Citation
“…SREBP1, like other SREBPs, is activated by a reduction of intracellular cholesterol, indicating a homeostatic link between fatty acid synthesis and cholesterol synthesis [108,109]. De novo fatty acid synthesis is critical for the correct formation and growth of myelin both in the PNS and in the CNS [33,48,[110][111][112]. Animals ablated for fatty acid synthase (encode by Fasn) in either Schwann cells or oligodendrocytes present a partial block in the onset and efficiency of myelination.…”
Section: Fatty Acid Synthesismentioning
confidence: 99%
“…Recently, fatty acid uptake was proposed to compensate partially for deficiencies in fatty acid synthesis in both the CNS and the PNS [110,111]. Compensation by fatty acid uptake was more evident in myelinating cells in direct proximity to blood vessels or indirectly from an increase in horizontal flux of fatty acids through astrocytes or adipocytes [33,110].…”
Section: Fatty Acid Uptakementioning
confidence: 99%
“…The analysis of this mouse model demonstrated that the major source of myelin lipids are astrocytes. [10] However, when lipid synthesis is inactivated in astrocytes, OLs are able to bypass this deficiency by recruiting dietary lipids for myelin membrane synthesis [22].…”
Section: Biosynthesis Of Fatty Acids and Sphingolipidsmentioning
confidence: 99%
“…However, the role of modulators of lipid metabolism in OPC-mediated repair is still not completely elucidated. Of note, recent studies suggest that targeting the lipid pathways in OLs may be a good strategy to promote remyelination [10].Furthermore, in MS, remyelination failure is also strictly correlated to an altered extracellular signaling microenvironment that, among others, affects the organization of OL membranes, which causes defects in myelin at the molecular level [11,12]. Although the ECM is one of the main elements that constitute the central nervous system (CNS) parenchyma, new roles for the ECM components in regeneration and repair responses to CNS injury have only recently been documented.…”
mentioning
confidence: 99%
See 1 more Smart Citation